Integrated analysis of genetic, proteinic, and metabolomic alterations in Behcet’s disease - Yanlin Pu; Jing Liang; Yao Wang; Wanyun Zhang; Chuiren Zhou; Ju Shao; Jin Hu; Minghui Chen; Yunjie Shi; Yongdan Mao; Zhijun Chen (Scientific Reports)
Abstract Numerous studies have investigated the alterations of genes, proteins, and metabolites in Behcet’s disease (BD). By far, little is known about the depiction of panoramic changes underlying this disease. This study purposed to assess the consistently dysregulated genes, proteins, and metabolites in BD across publications using the vote-counting approach. This study was based on 745 studies that identified a collection of 2354 differential molecules with 3574 molecule entries in blood, peripheral blood mononuclear cells, CD4+T cells, and aqueous humor samples from patients with BD. In this study, the results of binomial analysis showed that the circulating levels of 38 molecules, including interferon-γ and interleukin 17, were consistently upregulated, whereas high density lipoprotein cholesterol, apolipoprotein A, hemoglobin, and glutathione were consistently downregulated. The levels of interferon-γ, tumor necrosis factor-α and toll like receptor 4 in peripheral blood mononuclear cells, and interferon-γ and interleukin-17 in CD4+T cells were consistently upregulated. Additionally, the levels of interferon-γ, tumor necrosis factor-α and C-X-C motif chemokine ligand 8 in aqueous humor were consistently upregulated. Collectively, this study showed that the hyperactivity of Th1 and Th17 responses played an essential role in the pathogenesis of BD, and the progression of this disease was associated with enhanced neutrophil chemotaxis, vascular endothelial injury, activation of haemostatic system, and oxidative stress.